2017
DOI: 10.1108/ijse-01-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic communities: a factor of industrial clustering

Abstract: Purpose This paper not only draws conclusions from the available literature but also offers some new factors as well, which are not included in the existing literature. To be more precise, the purpose of this paper is to ascertain factors behind the clustering of the motorcycle industry, a low-tech and low investment industry. This paper weighs the government’s policies, role of factors of production, infrastructure, geography and other drivers for the subject industry and associated industries in the geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This suggests that the successful development and implementation of regional development strategies demands careful consideration of several local‐specific conditions (Porter, ). In line with the above discussion, Kamran et al () investigated the industrial clusters in Pakistan and claimed that for a high growth trajectory, the domestic investment environment, political instability, and regulations must be improved. Specifically, the authors analyzed the role of classical factors of production (including land, labor and capital), and found that a better infrastructure, availability of utility services, and the accessibility to inexpensive bank loans and commercial finance (Dumon, ) helped businesses in the developing economies to flourish in geographic proximities (Ahmed & Jhandir, ).…”
Section: Theoretical Backgroundmentioning
confidence: 90%
See 2 more Smart Citations
“…This suggests that the successful development and implementation of regional development strategies demands careful consideration of several local‐specific conditions (Porter, ). In line with the above discussion, Kamran et al () investigated the industrial clusters in Pakistan and claimed that for a high growth trajectory, the domestic investment environment, political instability, and regulations must be improved. Specifically, the authors analyzed the role of classical factors of production (including land, labor and capital), and found that a better infrastructure, availability of utility services, and the accessibility to inexpensive bank loans and commercial finance (Dumon, ) helped businesses in the developing economies to flourish in geographic proximities (Ahmed & Jhandir, ).…”
Section: Theoretical Backgroundmentioning
confidence: 90%
“…Considering these complex challenges, it seems that, despite excessive interest by the developing countries to apply industrial clusters, the effectiveness of the clustering concept remains questionable (Tan, 2006). For the micro-level challenges, the effect of context attributes to implement a cluster was revealed, which highlighted the role of the domestic environment as a success factor industrial cluster (Kamran et al, 2017). Our analysis unpacks how the contextual factors, such as poverty level, investment charming, people attitude, and labor and financial situations can adversely affect the cluster performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of clusters in developing countries have focused on the supportive role of government and public agencies on clusters’ performance (Richardson, 2013; Kamran et al , 2017), indicating for example that when the social bonding in a given cluster is weak, government interventions are of greater significance. The role of classical factors of production (including land, labour and capital) is analysed by Kamran et al (2017) and subsequently found that better infrastructure, availability of utility services and the accessibility to inexpensive bank loans and commercial finance helped businesses in developing countries flourish in geographic proximities. Richardson (2013) mentions that it would be great if the policymakers foresee the problems prior to developing the cluster and can take the necessary steps to address them.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The review of the cluster literature reflects, although a host of studies have examined clusters in developed countries (Kamran et al , 2017; Vanzettine et al , 2017), that a lack of research that systematically addresses the dynamics and nature of cluster development in developing economies is still problematic, especially small and medium-sized enterprises (SMEs) (Van Dijk and Rabellotti, 1997; Schmitz and Nadvi, 1999; Park and Luo, 2001; Lin et al , 2009; Pyke and Lund-Thomsen, 2016; Vanzettine et al , 2017). Researchers have identified this research gap, subsequently calling for more research to investigate the transferability of current theories of clusters to developing countries (Ghauri and Santangelo, 2012; Vanzettine et al , 2017).…”
Section: Introductionmentioning
confidence: 99%